Analisis Kalimat Ungkapan Kemarahan Dalam Bahasa Minangkabau di Kanagarian Muaro Paiti - Laili, Iman; Nelfi, Eriza; Alsumainitia, Alsumainitia (Fakultas Sastra Universitas Ekasakti, 2025)
This paper examines the sentence forms used to express anger in the Minangkabau language. It aims to describe the forms of sentences expressing anger based on the number of clauses that form them. This paper uses a qualitative descriptive approach. Data analysis was conducted using the theory proposed by Chaer and Sugono. Data were collected through the listening method with note-taking techniques. Furthermore, the distribution method with the simple deletion and close simple permutation techniques was used to analyze the data. Based on the analysis, two forms of sentences expressing anger were identified: simple sentences, consisting of one clause, and extended sentences composed of several clauses, namely two clauses, three clauses, and four clauses.